Pengaruh kepuasan kerja terhadap turnover intention pada karyawan sales PT. Dipo Internasional Pahala Otomotif Jambi - Dita Anastia; Zulfina Adriani; Rts Ratnawati (Jurnal Dinamika Manajemen, 2021)
The purpose of this study was to determine the effect of job satisfaction on turnover intention in PT. Dipo Internasional Pahala Otomotif Jambi. This type of survey research with a quantitative approach. The sample in this study were 42 sales employees in PT. Dipo Internasional Pahala Otomotif. Samples were taken with the Slovin formula. Data were collected by using a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple regression. The results of this study, it is known that the level of employee job satisfaction has a significant negative effect on the occurrence of turnover intention. The higher the job satisfaction, the lower the level of turnover intention in the company. Based on the results of this study, it is expected that PT. International Pahala Otomotif Dipo to maintain employee job satisfaction so that employees are not comfortable working and there is no intention to leave the company.